The awakening - Roberts, Nora (New York : St. Martin's Press, 2020)
Breen Kelly's father dissapeared when she was young. Lately she has noticed a silver-haired man following her. While house sitting for her mother, she finds records of a multimillion dollar inheritance in her name. When she flies to Ireland to claim what is rightfully hers, she enters a magical land of faeries, elves, and mermaids. Will she have the courage to embrace this new land and her destiny?
Series numbering from book jacket.
Keywords: Interdimensional travel -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Heiresses -- Fiction; Imaginary places -- Fiction; Ireland -- Fiction; Romance fiction; Fantasy fiction